Antibiotic resistance and rational outpatient antibiotic treatment of upper respiratory tract infections in children (Perioperaciina Medicina, 2023)
On the eve of the season of respiratory infections, we would like to draw the attention of outpatient doctors to the fact that 80–90 percent of winter diseases affecting the nose, ears, throat and lungs are of viral origin. Improper and excessive consumption of antibiotics increases the risk of antibiotic resistance, and thus humanity enters the post-antibiotic era. The World Health Organization warns that the problems that antibiotic resistance could cause in the future can be compared to the spread of AIDS in the 1980s. The principles of rational use of antibiotics should always be based on the assumption that antibiotics are causal drugs, and their overuse very often leads to resistance, which negatively affects the entire population. Irrational antibiotic therapy can also lead to discomfort, worsening of acute and chronic pain. It is also important to know that in the post-antibiotic era, science has other options for fighting bacteria, such as vaccination, immunotherapy, and strengthening individual immunity. The correct attitude of doctors to the prevention of diseases and rational treatment with antibiotics can help reduce the resistance of bacterial strains, discomfort and pain.
Keywords: antibiotics; vaccination; post-antibiotic era; resistance; season of respiratory diseases; pain; discomfort